Orientation to the Future and Academic Lag as Predictors of Academic Performance of High School and University Students in Northwest Mexico - Pérez-Ríos, Rubén (2023)
Introduction. Academic performance plays an important role in learning and acquiring personal knowledge that guides students towards effective development in their lives and future careers. Multiple factors influence their determination and contribute to knowing the state of quality education. Objetive. This research aimed to determine the relationship between orientation to the future, academic lag, and their impact on academic performance and to compare the results based on sex and academic level. Methodology. A total of 453 students participated in this non-experimental, cross-sectional, explanatory study and completed an instrument that included validated scales of orientation to the future and academic lag. Academic performance was measured by the accumulated average of grades. Results. The results show significant differences regarding sex and academic level. They also indicate that the academic performance of high school and college students is positively associated with orientation to the future and negatively with academic lag. The results of the structural model suggest that orientation to the future and academic lag predict academic performance. Discussion. These findings confirm the influence of personal variables on academic performance and reaffirm the value of orientation to the future in understanding students’ academic success.